Erronka(s) and a Transdisciplinary Approach for Basque Studies - Gaztañaga, Julieta (2023)
This article analyses the social praxis of ‘erronka’ aiming to contribute to the promotion of a transdisciplinary perspective for Basque Studies. In the Basque setting erronkas are typically understood as challenges and defies leading to betting and gambling, associated with games, sports, and physical and ingenious endeavors. Drawing from my long-term ethnography of Basque contemporary grass-root mobilizations for rights to self-determination, I inquire about the transdisciplinary approach in the search for answers about the role erronkas play in prefiguring political projects. The article proceeds in three steps. the opening section offers a brief theoretical framework of the broader issue of Basque studies and the transdisciplinary approach. The second and third sections are oriented to adopt such an approach to organize the analytics of erronkas examining respectively erronkas in general and a particular case of political erronka by focusing on Korrika, a popular and massive footrace to promote Basque language. Finally, it argues that a transdisciplinary perspective is needed to shed some light onto the collective role of erronkas, particularly those attached to sovereigntists claims and the realizations of political imagination.